Body Image dan Peran Keluarga Remaja Status Gizi Lebih di Kota Malang - Febriani, Reny Tri (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
Nutritional status is more a health problem in developing countries. More nutritional status causes heart disease, hypertension and diabetes mellitus, psychological problems such as cognitive delay, withdrawal from the social environment which will disrupt the growth and development of adolescents. The prevalence of adolescent over nutritional status in 10 state high schools in Malang City is 502 students. The role of parents has an increased factor in the prevalence of nutritional status more related to consumption patterns, as well as more nutritional status adolescents have a negative body image. Research to analyze the role of families that cause more nutritional status and body image of adolescents with more nutritional status. The analytic observational research design was cross sectional approach. Respondents 111 overweight and obese teenagers in 10 public high schools in Malang. Random sampling and proportional sampling techniques. The study was conducted in February - March 2018. Data analysis used SmartPLS version 3. The results showed that most of the family's role included high allowance and socio-economic costs of respondents, working mothers and negative body image in adolescents with more nutritional status. The role of the family affects the nutritional status of adolescents (t statistic 5,072, p value 0,000). Nutritional status is more influential on adolescent body image (t statistic 25,812, p value 0,000). The role of the family influences consumption patterns and obese adolescents have a negative body image.